P03.15 Site-specific immune evasion and substantial heterogeneity within entities provide evidence for personalized immunotherapy. (1st October 2020) - Thelen, M; Wennhold, K; Lehmann, J; Staib, E; Garcia Marquez, MA; Lohneis, P; Lechner, A; Wagener-Ryczek, S; Plum, PS; Pfister, D; Dörr, F; Beutner, D; et al.
Abstract : Background: Immune-checkpoint inhibition (CKI) demonstrated remarkable therapeutic efficacy in several kinds of cancer. However, immune escape mechanisms lead to primary or secondary resistance in the majority of patients. Most predictive biomarkers failed, as the primary target of CKI is not the tumor cell itself, but the crosstalk between immune- and cancer cells. We aimed to characterize the immune evasion landscape in primary tumors across different entities. Materials and Methods: Expression of 32 immune-regulatory molecules on lymphocytes was analyzed in peripheral blood and tumor infiltrating lymphocytes (TILs) of 146 primary tumor patients across 10 different entities using flow cytometry. NanoString was applied to determine RNA expression of the respective ligands and 20 genes associated with antigen presentation. Expression of coinhibitory ligands on tumor cells was assessed by immunohistochemistry. To quantify the immune cell infiltration, digital pathology was used and the Immunoscore was generated for each patient. Results: While an increase of regulatory T cells was a common feature across all entities, we found site-specific differences regarding other lymphocyte subsets and expression of immune-regulatory molecules by TILs and tumor cells. Expression of co-inhibitory molecules on tumor infiltrating T cells accumulated especially in advanced stage cancers whereas immune cell infiltration was mainly associated with enhanced antigen presentation. Co-expression of multiple immune-inhibitory ligands was most frequent in colorectal, lung and ovarian carcinoma. Genes related to antigen presentation were frequently dysregulated in seminoma, liver and lung cancer. Conclusions: Immune evasion is a common feature of cancer and frequently detected co-occurrence of multiple mechanisms probably contributes to resistance against immunotherapy. We describe substantial heterogeneity regarding immune escape mechanisms between patients with the same primary tumor. Individualized immunotherapeutic strategies based on pretherapeutic evaluation of the immune evasion landscape might help to improve response to CKI. Disclosure Information: M. Thelen: None. K. Wennhold: None. J. Lehmann: None. E. Staib: None. M.A. Garcia Marquez: None. P. Lohneis: None. A. Lechner: None. S. Wagener-Ryczek: None. P.S. Plum: None. D. Pfister: None. F. Dörr: None. D. Beutner: None. F. Thangarajah: None. D. Ratiu: None. W. Malter: None. S. Merkelbach-Bruse: None. C.J. Bruns: None. A. Quaas: None. M.S. von Bergwelt-Baildon: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; Astellas. F. Consultant/Advisory Board; Modest; Bristol-Myers Squibb. H.A. Schlößer: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; Astra Zeneca.